2011
DOI: 10.2217/imt.11.122
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Blockade in Inflammatory Bowel Diseases

Abstract: Inflammatory bowel diseases (IBDs) are chronic disabling diseases with significant morbidity. A deregulated immune response towards the intestinal microbiota is thought to play an important role in the pathogenesis of IBD, and thus biological therapies targeting key molecules such as cytokines have been designed. Several anti-TNF-α agents are currently being used to treat Crohn's disease and ulcerative colitis. Although these molecules dramatically improved the treatment of patients, side effects and the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 97 publications
2
52
0
1
Order By: Relevance
“…The increased proinflammatory cytokines such as TNF- α , IFN- γ , and IL-1 β amplify the inflammatory cascade and result in intestinal tissue damage in UC induced by DSS [32]. Among those cytokines, the overexpression of TNF- α is vital in intestinal mucosal impairment [33].…”
Section: Discussionmentioning
confidence: 99%
“…The increased proinflammatory cytokines such as TNF- α , IFN- γ , and IL-1 β amplify the inflammatory cascade and result in intestinal tissue damage in UC induced by DSS [32]. Among those cytokines, the overexpression of TNF- α is vital in intestinal mucosal impairment [33].…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of IBD has more recently been revolutionized by the development of targeted molecular agents with the use of therapeutic antibodies against TNFalpha (anti-TNF) to suppress mucosal inflammation. 17,18 The step-up approach for the treatment of IBD has been challenged with the emergence of such 'biologic' agents and a 'top-down' therapeutic paradigm has been proposed, which advocates early aggressive use of therapeutic antibodies as a first line of treatment. 19 However, early use of therapeutic antibodies, typically combined with immunomodulators to promote mucosal healing may also lead to increased risk of toxicity, infections and the rare risk of hepatosplenic T-cell lymphoma in young men.…”
Section: Inflammatory Bowel Disease (Ibd)mentioning
confidence: 99%
“…Although the pathogenesis of IBD remains unclear, a number of studies have suggested the involvement of abnormal apoptosis in intestinal epithelial cells, resulting from increased production of cytokines, such as TNF, ILs, and IFNs (2). TNFa is a key mediator of inflammation in IBD and has been the primary target of biologic therapies (3). This cytokine induces inflammation by promoting the production of IL1b and IL6, expression of adhesion molecules, proliferation of fibroblasts, activation of procoagulant factors, and cytotoxicity of the acute phase response (4).…”
Section: Introductionmentioning
confidence: 99%